Antireflective Self-Cleaning TiO2 Coatings for Solar Energy Harvesting Applications - Afzal, Adeel; Habib, Amir; Ulhasan, Iftikhar; Shahid, Muhammad; Rehman, Abdul (Frontiers in Materials, 2021)
Titanium(IV) oxide (TiO2, titania) is well-known for its excellent photocatalytic properties, wide bandgap, chemical resistance, and photostability. Nanostructured TiO2 is extensively utilized in various electronic and energy-related applications such as resistive switching memory devices, flat panel displays, photodiodes, solar water-splitting, photocatalysis, and solar cells. This article presents recent advances in the design and nanostructuring of TiO2-containing antireflective self-cleaning coatings for solar cells. In particular, the energy harvesting efficiency of a solar cell is greatly diminished by the surface reflections and deposition of environmental contaminants over time. Nanostructured TiO2 coatings not only minimize reflection through the graded transition of the refractive index but simultaneously improve the device’s ability to self-clean and photocatalytically degrade the pollutants. Thus, novel approaches to achieve higher solar cell efficiency and stability with pristine TiO2 and TiO2-containing nanocomposite coatings are highlighted herein. The results are compared and discussed to emphasize the key research and development shortfalls and a commercialization perspective is considered to guide future research.